Aqueous distillate of mature leaves of Vernonia zeylanica (L.) Less. and Mallotus repandus (Rottler) Müll. Arg. cued from traditional medicine exhibits rapid wound healing properties - Ratnayake, Praneeth; Samaratunga, Udaya; Perera, Inoka C.; Seneviratne, Jayamini; Udagama, Preethi (Journal of Ethnopharmacology, 2024)
Ethnopharmacological relevance: Sri Lankan traditional medicine uses Vernonia zeylanica and Mallotus repandus broadly for the treatment of a multitude of disease conditions, including wound healing. Aim of the study: We aimed to scientifically validate the safety and efficacy of wound healing of an aqueous distillate of Vernonia zeylanica and Mallotus repandus (ADVM) mature leaves, tested on primary human dermal f ibroblasts. Materials and methods: Human dermal fibroblasts isolated from clinical waste from circumcision surgery were characterized by flowcytometry and trilineage differentiation. The MTT dye reduction assay, and the ex vivo wound healing scratch assay established wound healing properties of ADVM using the primary human dermal f ibroblast cell line. Upregulation of genes associated with wound healing (MMP3, COL3A1, TGFB1, FGF2) were confirmed by RT qPCR. GC-MS chromatography evaluated the phytochemical composition of ADVM. Results: Compared to the synthetic stimulant, β fibroblast growth factor, ADVM at 0.25% concentration on the primary dermal fibroblast cell line exhibited significant ex vivo, (i) 1.7-fold % cell viability (178.7% vs 304.3 %, p < 0.001), (ii) twofold greater % wound closure (%WC) potential (47.74% vs 80.11%, p < 0.001), and (iii) higher rate of % WC (3.251 vs 3.456 % WC/h, p < 0.05), sans cyto-genotoxicity. Up regulated expression of FGF2, TGFB1, COL3A1 and MMP3, genes associated with wound healing, confirmed effective stimulation of pathways of the three overlapping phases of wound healing (P < 0.05). GC-MS profile of ADVM characterized four methyl esters, which may be posited as wound healing phytochemicals. Conclusions: Exceeding traditional medicine claims, the ex vivo demonstration of rapid skin regeneration, reit erated by upregulated expression of genes related to wound healing pathways, sans cytotoxicity, propounds ADVM, cued from traditional medicine, as a potential safe and effective natural stimulant for rapid wound- healing. Additionally, it may serve as an effective proliferative stimulant of dermal fibroblasts for cell ther apy, with potential in reparative and regenerative therapy of skin disorders.
Keywords: Wound healing, Aqueous herbal distillate, Vernonia zeylanica, Mallotus repandus, Primary human dermal fibroblasts, Skin regeneration